2022
DOI: 10.1186/s12889-022-13419-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary fiber intake and atherosclerotic cardiovascular disease risk in adults: a cross-sectional study of 14,947 population based on the National Health and Nutrition Examination Surveys

Abstract: Background This study aimed to investigate the association between dietary fiber intake and long-term cardiovascular disease (CVD) risk based on the National Health and Nutrition Examination Survey (NHANES) database. Methods A total of 14,947 participants aged 20–79 from the NHANES database were included in this study between 2009 and 2018. The atherosclerotic cardiovascular disease (ASCVD) score was utilized to predict the 10-year risk of CVD in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…However, a 2021 US study [28] suggested dietary fiber was independently associated with a reduced risk of diastolic hypertension (OR = 0.848, 95% CI 0.770, 0.934) and systolic hypertension (OR = 0.906, 95% CI 0.826, 0.993) after adjustments were made for confounding factors. On the relationship between dietary fiber intake and the risk of cardiovascular disease, a 2016 Iranian study [7] and a 2022 study from NHNES [29] suggested a negative association between fiber intake and the development of cardiovascular disease, but a 2020 French study [13] concluded that dietary fiber intake was not associated with the development of cardiovascular disease (OR = 0.86, 95% CI: 0.70, 1.06). On the relationship between dietary fiber intake and the risk of obesity development, a 2010 European study [8] suggested that total fiber intake was negatively associated with increased body weight and waist circumference.…”
Section: Discussionmentioning
confidence: 99%
“…However, a 2021 US study [28] suggested dietary fiber was independently associated with a reduced risk of diastolic hypertension (OR = 0.848, 95% CI 0.770, 0.934) and systolic hypertension (OR = 0.906, 95% CI 0.826, 0.993) after adjustments were made for confounding factors. On the relationship between dietary fiber intake and the risk of cardiovascular disease, a 2016 Iranian study [7] and a 2022 study from NHNES [29] suggested a negative association between fiber intake and the development of cardiovascular disease, but a 2020 French study [13] concluded that dietary fiber intake was not associated with the development of cardiovascular disease (OR = 0.86, 95% CI: 0.70, 1.06). On the relationship between dietary fiber intake and the risk of obesity development, a 2010 European study [8] suggested that total fiber intake was negatively associated with increased body weight and waist circumference.…”
Section: Discussionmentioning
confidence: 99%
“…Higher dietary fiber density was most associated with a lower risk of atherosclerotic cardiovascular disease in people aged 20-39 and 40-59 years. Young people may benefit more from high dietary fiber intake for protection against CVD, i.e., dietary fiber intake of 14 g/1000 kcal had a better protective effect in this age group [41].…”
Section: Dietary Fibermentioning
confidence: 95%
“…Shim et al [26] and Duchame-Smith et al [27] pointed out that diet may be an important factor in BP control in patients with hypertension. Some bioactive ingredients may explain the cardioprotective effects of diet, such as vitamins, essential elements, dietary fiber, and phytochemicals [28][29][30][31]. The potential mechanisms of action may involve antioxidation; anti-inflammation; and regulation of blood sugar, blood lipids, and BP [32,33].…”
Section: Principal Findingsmentioning
confidence: 99%